EXPERIENCE-BASED CAREER EDUCATION: MODEL ALTERNATIF PEMBELAJARAN KETERAMPILAN DI SLTP - Endang Mulyatiningsih (LPMPP Universitas Negeri Yogyakarta, 2004)
The Experience-Based Career Education (EBCE) learning model aimsto relate learning activity to real experience inthe field. This learning model is appropriately applicable on skill subject matter classes with limited facilities, time, students' motivation, andteachers' ability. Classes with such characteristics are commonly found at junior high schools teaching such subject matter as a local content school subject. The EBCE learning model makes use ofthe learning resources available in society. The selected learning resources can be those belonging to anindividual, anorganization, and society. Inthe teach ing activity teachers act as learning coordinators. Thematerials stu dents can learn are those about career-related knowledge and skills in accordance with their interests. The students planthe learning ac tivity in the form ofa project ofwhich the result can be demonstrated in front ofthe class. The EBCElearning model is recommended only as a supple mentary learning model to the existing ones. This model can be applied on other subject matter with similar characteristics. Ifthis model is appropriately implemented, it will enhance students' career understanding, which has become everyone's primary need. Key words: skill, career education, learning model